Clima e turismo no município de Botucatu-SP - Mena, Fábio Eduardo de Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2004)
A pesquisa Clima e Turismo no Município de Botucatu (SP) teve como objetivo principal analisar as características climáticas de Botucatu, com base nos dados dos parâmetros meteorológicos: temperatura e precipitação pluviométrica cedidos pela Estação Meteorológica da UNESP - Campus de Lageado. Analisou-se também, o Plano Diretor de Turismo para o Município de Botucatu (2001), procurando apresentar os recursos naturais, os patrimoniais, os históricos-arquitetônicos e os recursos públicos, em conjunto com os recursos climáticos favoráveis para o turismo sustentável na região.

The research Weather and Tourism in Botucatu County had as its main aim the analysis of the weather characteristics of Botucatu (SP) with basis on the data of following weather parameters: temperature and water precipitation supplied by the Weather Forecasting Station of UNESP - Lageado Campus. It was also analyzed the Tourism Directive Plan for Botucatu County (2001) aiming to show the natural resources, the patrimonial resources, the historical - architectonical resources and the public resources together with the favorable weather resources for the uphold able tourism in the region.
Keywords: Climatologia; Climatologia geográfica; Recursos climáticos; Turismo sustentável; Recreação e Lazer; Geografia do turismo; Geography Tourism; Recreation and Leisure